2001
DOI: 10.9774/gleaf.3062.2001.au.00006
|View full text |Cite
|
Sign up to set email alerts
|

Horses for Courses

Abstract: Researchers and policy-makers have become increasingly enthusiastic about greening purchasing and supply management activities. In theory, greening supply should both limit environmental damage from industrial activities and deliver bottom-line benefits to implementing firms. However, compared with other environmental initiatives, few firms have implemented extensive green supply programmes.This paper seeks to resolve the apparent paradox between the desirability of green supply in theory and the slow implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Communication between business managers and environmental professionals is also important in the successful business and environment relationship (Aspan 2000). The internal green management dimension also includes processes such as environmental auditing of departments, environmental management systems, total quality environmental management, and communication and training (Bowen et al 2001;Klassen and Whybark 1999;Sarkis, Gonzalez-Torre, and Adenso-Diaz 2010;Zhu, Sarkis, and Lai 2008).…”
Section: Internal Green Managementmentioning
confidence: 99%
“…Communication between business managers and environmental professionals is also important in the successful business and environment relationship (Aspan 2000). The internal green management dimension also includes processes such as environmental auditing of departments, environmental management systems, total quality environmental management, and communication and training (Bowen et al 2001;Klassen and Whybark 1999;Sarkis, Gonzalez-Torre, and Adenso-Diaz 2010;Zhu, Sarkis, and Lai 2008).…”
Section: Internal Green Managementmentioning
confidence: 99%
“…[17,31] Also, this paper includes the relationship between the environment and competitive advantage, which has been studied extensively. [4,17,21,32] Early studies focused on the reaction of environmental regulations aimed at reduce and minimizing harmful environmental outcomes. [33] Unfortunately this research chiefly viewed greening as unproductive investments.…”
Section: Green Supply Chain Practicementioning
confidence: 99%
“…[2,20] Studies have sought to find solutions to the paradox between the desirability and the actual slow implementation of GSCM practices. [21] Several studies have identified antecedents of "greening" as reactive to the changing business environment, such as regulatory compliance, stakeholder pressures and ethical concerns. [22] However, an independent body of research in recent years has led to the view that antecedents of "greening" are proactive corporate strategies (i.e., market orientation).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that there is a mix of both negative and positive impacts by green supply chains on economic performance [78,79]. Some researchers claims that green purchasing (a subset of green supply chains) may enhance short-term cost savings and positively impact brand image, which will lead to enhanced economic performance [49].…”
Section: Sustainable Supply Chainsmentioning
confidence: 99%